Slovenistika 10. Zbornik predavanj. Ur. Mária Bajzek Lukácsné: Budimpešta: ELTE BTK, Szláv Filológiai Tanszék. 230 str. - Ulčnik, Natalija (Slavia Centralis, 2020)
The paper presents a collection of lectures with papers from an international conference held on 26 October 2016. It was edited by Marija Bajzek Lukač.
Keywords: Slovenian studies; Slovenian language; Slovenian literature; Slovenian-Hungarian cultural contacts; proceedings; review; report